Contraceptive Choices, Pregnancy Rates, and Outcomes in a Microbicide Trial - Sibeko, Sengeziwe (2011)
OBJECTIVE: Women who become pregnant during the conduct of biomedical HIV prevention trials are taken off the study product for safety reasons. High pregnancy rates can compromise statistical integrity in these trials. The comprehensive contraceptive curriculum developed for the Centre for the AIDS Programme of Research in South Africa (CAPRISA) 004 trial was evaluated for its ability to enhance contraceptive uptake, reduce pregnancy rates, and preserve statistical integrity. METHODS: Contraceptive- and pregnancy-related eligibility criteria were specified in the protocol. We enrolled women who opted for a non-barrier method of contraceptive and provided hormonal contraceptives on-site at no cost. At each monthly study visit, we provided pregnancy prevention counselling and performed pregnancy testing. Study product was withheld on pregnancy diagnosis, but women continued with monthly follow-up. RESULTS: Contraceptive usage was high throughout the study with 100% uptake at baseline and 94.71% use after a mean of 18 months follow-up at exit. Injectable progestins, particularly medroxyprogesterone acetate, remained the preferred choice of contraceptive. After 30 months of follow-up, 54 pregnancies were reported out of 889 participants, giving a pregnancy incidence rate of 3.95 per 100 woman-years (95% CI: 2.96 to 5.17). Of all pregnancies, 2/3 (64.81%) resulted in a full-term live birth, while 18.52% and 11.11% pregnancies culminated as miscarriage and terminated pregnancies, respectively. There were no congenital anomalies in the early neonatal period. Pregnancies resulted in 1.56% of woman-years of study follow-up lost due to temporary product withdrawal. CONCLUSION: The CAPRISA 004 contraceptive curriculum was an effective strategy for maintaining low pregnancy rates, thereby minimizing product withdrawal and loss of follow-up time.